Exploring Factors That Impact Oral Communication And Establishing Oral Skill Standards In A University In The UAE - Abdulqader, Myasar Mohammed (2020)
Oral communication skills in English are vital in academic studies for the students in which the medium of teaching is English. Mastering oral English skills enables the students in a university to participate and achieve their tasks effectively and successfully. Assessing speaking is not less significant than teaching it. It is so important that English instructors assess their students in speaking to determine their proficiency. Therefore, the study addressed two issues. The first part of the study is to examine to what extent pronunciation, vocabulary knowledge and exposure to English impact on oral communication of students in a university in the United Arab Emirates (UAE). The second part of the study is to establish standards for assessing speaking skill of university students as to be based on in specifying students’ levels. The study used testing, questionnaire as quantitative method and semi-structured interview as a qualitative method to collect required data. SPSS was utilized to analyse data and the study came out with significant correlation at 0.01 and 0.05 levels between pronunciation, vocabulary knowledge and exposure to English and oral communication skills proficiency. The study used OPI (Oral Proficiency Interview) to assess participants in speaking against 5 criteria including factors that impact on oral communication (pronunciation, vocabulary, comprehension) as well as grammar and fluency. SPSS was used to analyse data and came out with 6 levels. The target population of the study were students studying in English Language Institute at American University in the Emirates in the UAE country. The study involved all 200 students who were all accessible to this study. The findings of the study are hoped to enable instructors to focus on said factors in teaching English in university in the UAE as to improve the students’ performance in oral communication. Whereas establishing standards for speaking assessment is hoped to be a guideline not only for English instructors in university but also for ministry of education to categorize English learners into levels based on a solid benchmark. Several recommendations were made in relation to this study in the last chapter of the research.